International Tourism, Financial Deepening and Economic Growth: Insights from Southern African Countries - MISHRA, P. K.; ROUT, Himanshu B.; SAHOO, Debasis; KUMAR, Pradip; CHAINI, S. R. (Theoretical and Practical Research in Economic Fields, 2023)
The impact of tourism development on financial development via its effects on economic growth and country openness in Southern African countries for the period 1995 to 2019 was examined relying on pooled mean group-based estimation of panel ARDL regression, and the results lend supports to the tourism-led financial development hypothesis in these countries in the long-run. The findings infer that the development of the travel and tourism sector can spur financial development as the former by contributing to output, employment and income warrant an enhanced role of the financial sector.